Effects of UV-C radiation on common dandelion and purple coneflower: First results (International Journal of Plant Biology, 2017)
Ultraviolet-C (UV-C) light (100 ≤ λ ≤ 280 nm) is a ionizing radiation that can damage living organisms. An experiment was conducted on plants of common dandelion (Taraxacum officinale Weber, T. Densleonis Desf.) and purple coneflower [Echinacea purpurea, (L.) Moench] irradiated with UV-C at different exposition times, under controlled conditions and grown in self-produced characterized compost, to assess the effect of different doses UV-C radiation on some physiological parameters. Trials have been carried out using a black chamber equipped with an UV-C lamp in which plants were divided in four groups on the basis of UV-C irradiation period (10, 30, 60, and 120 min). Non-irradiated plants were kept as controls. Plant photosynthetic performance, chlorophyll content (SPAD) and some morphologic traits were recorded before, immediately after irradiations and 20 days weeks later. The effects on photosynthetic performances and chlorophyll contents (SPAD) were evaluated and compared with data obtained in similar experiments where tomato plants were irradiated at different times with UVC light. In both species, SPAD values decreased as the irradiation period became longer. The two species showed different gas exchange dynamics, depending on the UV-C exposure time. Two months after the UV-C irradiation, plant dry weight measured at 120-min UV-C exposure was significantly lower than the control.